This land is your land - Guthrie, Woody, 1912-1967.; Jakobsen, Kathy (Boston, MA : Little, Brown, 1998)
This well-known folk song is accompanied by a tribute from folksinger Pete Seeger, the musical notation, and a biographical scrapbook with photographs.
Map on endpapers.
Wilson's Children
School Library Journal starred
Notable/Best Books (A.L.A.)
2.8
K-3
Keywords: Folk songs, English -- United States -- Texts; Folk songs -- United States; Folk songs -- United States